2012
DOI: 10.2147/ijn.s30104
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cellular uptake of activable cell-penetrating peptide–doxorubicin conjugate by enzymatic cleavage

Abstract: Abstract:The use of activable cell-penetrating peptides (ACPPs) as molecular imaging probes is a promising new approach for the visualization of enzymes. The cell-penetrating function of a polycationic cell-penetrating peptide (CPP) is efficiently blocked by intramolecular electrostatic interactions with a polyanionic peptide. Proteolysis of a proteinase-sensitive substrate present between the CPP and polyanionic peptide affords dissociation of both domains and enables the activated CPP to enter cells. This AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Cell-penetrating peptides (CPPs) are short peptides (<30 amino acids), often cationic and have the ability to internalize into the eukaryotic cells without causing significant membrane damage ( 1 2 ). Owing to this intrinsic cell-penetrating property, CPPs are capable of delivering conjugated therapeutic molecules like proteins ( 3 ), peptides ( 4 ), nucleic acid ( 5 8 ), small molecule drugs ( 9 ), nanoparticles ( 10 11 ), etc. to the cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-penetrating peptides (CPPs) are short peptides (<30 amino acids), often cationic and have the ability to internalize into the eukaryotic cells without causing significant membrane damage ( 1 2 ). Owing to this intrinsic cell-penetrating property, CPPs are capable of delivering conjugated therapeutic molecules like proteins ( 3 ), peptides ( 4 ), nucleic acid ( 5 8 ), small molecule drugs ( 9 ), nanoparticles ( 10 11 ), etc. to the cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…CPPs have remarkable ability to transverse eukaryotic membranes without significant membrane damage. In addition, CPPs can carry a variety of cargoes like peptides [4,5], proteins [6], drugs [7,8], nucleic acids [9,10], siRNAs [11,12], nanoparticles [13,14], etc. across the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, treatment of lung cancer cell lines positive and negative for MMP-9 demonstrated the ability of MMP-9 to significantly enhance DOX and PXL cancer cell cytotoxicity. Similar studies have shown the feasibility of this approach using an MMP-2/9 activatable DOX conjugated reagent to treat MCF-7 breast cancer cells and patient derived primary lung cancer cell lines [102,103].…”
Section: New Tools To Image Mmp Activity In Vivomentioning
confidence: 64%